The Influence of Strain Type and Female Age on the Receptivity of Female Drosophila melanogaster in Homogamous Crosses - Lisa Savitri; Kharisul Ihsan; Rochmad Krissanjaya; Elfred Rinaldo Kasimo (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Drosophila melanogaster is a widely used model organism in genetic research due to its short life cycle and the presence of many genes homologous to those found in humans. It plays an important role in studies related to genetic inheritance, gene interaction, sex determination, and developmental genetics. One key aspect of its reproductive biology is female receptivity—the willingness of a female to accept mating—which is influenced by various internal and external factors. External factors include environmental conditions such as temperature and humidity, as well as male courtship signals like wing vibrations and chemical cues. Internal factors are mainly related to the female's sexual maturity and mating status. Generally, female receptivity increases with age after eclosion, reaches a peak, and gradually declines. This study investigates the impact of strain type and female age on receptivity in homogamous crosses of D. melanogaster, using two mutant strains: dp (with a wing mutation) and wa (with an eye color mutation). Receptivity was measured by the presence or absence of F1 offspring following crosses between males and females of the same strain, with females tested at different ages ranging from 10 to 60 hours after eclosion. The results indicate that strain type does not have a significant effect on female receptivity. In contrast, female age plays a clear role: individuals aged 30 years and older were more receptive and more likely to produce offspring. No significant interaction was found between strain type and age. These findings suggest that female receptivity in D. melanogaster is more strongly influenced by sexual maturity (as indicated by age) than by genetic differences between strains.